Topographical and chemical effects of electrochemically assisted deposited hydroxyapatite coatings on osteoblast-like cells - Pegg, Elise C.; Matboli, Faisal; Marriott, Tim; Khan, Imran; Scotchford, Colin (SAGE, 2014)
A recently commercialised hydroxyapatite electrochemically assisted chemical deposition technique (BoneMaster) has been shown to induce increased bone apposition; whether this response is caused by the surface topography or chemistry is unknown. An in-vitro examination using human osteoblast-like cells was performed on a series of BoneMaster-coated surfaces. The chemistry was separated from the topography using a thin gold coating; Thermanox coverslips were used as a control. BoneMaster surfaces showed significantly greater alkaline phosphatase activity and osteocalcin production compared with controls; however, no difference was found between the gold-coated and uncoated BoneMaster samples, indicating topography is the main contributing factor.